Structural disruption increases toxicity of graphene nanoribbons. Issue 11 (16th September 2014) - Mullick Chowdhury, Sayan; Dasgupta, Subham; McElroy, Anne E.; Sitharaman, Balaji
ABSTRACT The increased utilization of graphene nanoribbons (GNRs) for biomedical and material science applications necessitates the thorough evaluation of potential toxicity of these materials under both intentional and accidental exposure scenarios. We here investigated the effects of structural disruption of GNRs (induced by low‐energy bath and high‐energy probe sonication) to in vitro (human cell lines), and in vivo (Oryzias latipes embryo) biological systems. Our results demonstrate that low concentration (20 µg ml−1) suspensions of GNRs prepared by as little as 1 min of probe sonication can cause significant decreases in the overall metabolic state of cells in vitro, and increased embryo/larval mortality in vivo, as compared to bath sonicated or unsonicated suspensions. Structural analysis indicates that probe sonication leads to disruption in GNR structure and production of smaller carbonaceous debris, which may be the cause of the toxicity observed. These results point out the importance of assessing post‐production structural modifications for any application using nanomaterials. Copyright © 2014 John Wiley & Sons, Ltd.